A rapidly expanding cutaneous tumour in the context of a Janus kinase inhibitor agent following allogeneic stem cell transplant. (25th August 2022) - Davies, Anna; Salisbury, Jon; Mehra, Varun; Papa, Sophie; Basu, Tanya
Abstract : Ruxolitinib is a selective, Janus kinase (JAK)1 and JAK2 inhibitor, which is effective in management of chronic graft‐versus‐host disease (cGvHD). However, the ensuing immunosuppressive effects can give rise to aggressive cutaneous tumours, including Merkel cell carcinoma. We present this case to highlight the development of cutaneous tumours with ruxolitinib, an increasingly used therapy, and the challenge of managing such tumours in the context of refractory cGvHD. Click here for the corresponding questions to this CME article.